A hardware demonstrator of a cognitive radio system using temporal opportunities - Biard, L.
Opportunistic radio (OR) systems usually identify and exploit unused spectrum resources in the frequency domain. Targeting opportunities in the time domain of course yields more stringent timing requirements for the opportunistic system, but enables a more optimized resource usage when spectrum opportunities are limited, like for unlicensed bands. This paper describes a hardware demonstrator of such an OR system detecting and using temporal opportunities, and particularly focuses on the key modules required to achieve the opportunistic functionality. To this end, it presents an exclusive implementation of a cyclostationarity sensing algorithm, and proposes a low complexity decision-making algorithm, which performs real-time regulation of the OR communications. Finally, it includes collaborative sensing features to address efficiently the hiddennode scenario. The demonstrator operates in the 2.4 GHz band, and has been validated by sharing the spectrum resource with a standard IEEE 802.11g primary system (PS) running a video streaming application, without perceptible impact of the OR system. It should finally be emphasized that the concepts and techniques undertaken can easily be transposed to any packet based transmission over OFDM or W-CDMA PHY.